Estudo da reação de hidrogenação de CO2 para a síntese de álcoois em catalisadores à base de Cu e Co - Oliveira, Francisco Marcelo dos Santos de (2024)
CO2 is a gaseous chemical compound important for maintaining life on Earth, being used in the photosynthesis process by plants, which forms glucose and releases oxygen into the atmosphere. Furthermore, it is the main greenhouse gas, a natural process that retains heat and keeps the Earth's surface warm, ensuring the necessary temperature and climate conditions to life. Anthropogenic activities such as the burning of fossil fuels, industrial processes, deforestation, and fires have increased the concentration of this gas in the atmosphere in recent years. Consequently, the greenhouse effect has intensified, increasing the planet's temperature, and resulting in anomalous climate phenomena, such as the melting of polar ice caps, rising sea levels, and more frequent episodes of drought, floods, storms and hurricanes in different regions. CO2 recycling technologies have been developed with the aim of reducing the emission of this gas and mitigating its effects on climate change. The catalytic hydrogenation of CO2 for the generation of products of commercial interest, such as methanol and ethanol, for example, is a technology that has attracted the attention of recent research, given the wide industrial applicability of these alcohols and the possibility of carbon recycling. In the present study, the CO2 hydrogenation reaction was investigated to produce alcohols using catalysts based on cobalt, copper and a combination between cobalt and copper. It was observed that CuO-Co3O4-Al2O3 catalysts with different Co:Cu mass ratios have improved methanol productivity when compared to CuO-Al2O3 or Co3O4-Al2O3, while ethanol was obtained only in Co3O4-Al2O3. The promotion of Co3O4-Al2O3 by the alkali metals Na, K, Rb or Cs with a mass content of 2% showed better catalytic performance for the formation of ethanol, with emphasis on 2%Na-Co3O4-Al2O3, which increased the ethanol productivity approximately 25 times compared to non-promoted material, while methanol productivity decreased with promotion by different alkali metals. Furthermore, the highest ethanol productivity in the present work, corresponding to 5.3 µmol/gcat.h, was achieved using the 2%K-Co3O4-Al2O3 catalyst under the reaction conditions of T = 220 °C, P = Patm and GHSV = 24,000 mL/gcat.h.